2002
DOI: 10.17221/10485-pps
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of incidence and determination of fungi on caraway, fennel, coriander and anise, consideration of disease importance and possibility of chemical protection

Abstract: The incidence of fungi on caraway (Carum carvi L.), fennel (Foeniculum vulgare Mill.), coriander (Coriandrum sativum L.) and anise (Pimpinella anisum L.) was observed on several localities in the Czech Republic. Incidence of 26 parasitic and saprophytic fungi were found on fennel, 35 species on coriander, 21 species on anise and 34 species on caraway. Small plot trials of spices were evaluated during the whole growing season. The fungicides in caraway were applied in different growth stages. The test results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Other fungal species belonging to Leptosphaeriaceae, as well as the closely related Didymellaceae (Odstrčilová et al 2002;Shaker and Alhamadany 2015) have been reported worldwide in fennel crops. In Italy, crown rot of fennel caused by Didymella glomerata (syn.…”
Section: Discussionmentioning
confidence: 99%
“…Other fungal species belonging to Leptosphaeriaceae, as well as the closely related Didymellaceae (Odstrčilová et al 2002;Shaker and Alhamadany 2015) have been reported worldwide in fennel crops. In Italy, crown rot of fennel caused by Didymella glomerata (syn.…”
Section: Discussionmentioning
confidence: 99%
“…Several diseases caused by fungi have been reported affecting fennel around the world, including Aureobasidium 2 pullulans, Alternaria spp., Ascochyta phomoides, Cladosporium spp., Botrytis cinerea, Diaporthe angelicae, Didymella glomerata, Didymospora sp., Dendryphion nanum, Colletotrichum gloeosporioides, Epicoccum purpurascens, Erysiphe heracleid, Fusarium spp., Fusoidiella anethi, Itersonilia pastinaceae, Gonatobotrys simplex, Macrophomina phaseolina, Melanconiales sp., Ochraceocephala foeniculi, Leptosphaeria purpurea, Periconia sp., Pythium sulcatum, Phytophthora megasperma, Ramularia foeniculi, Rhizoctonia solani, Sclerotium rolfsii, Sclerotinia spp., Stemphylium botryosum, Subplenodomus apiicola, and Volucrispora sp. (Odstrčilová et al, 2002;Khare et al, 2014;Erberk et al, 2019;Köse, 2019;Aiello et al, 2020). Curvularia species, on the other hand, have not previously been reported to be fennel pathogens.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…A. dauci (Kuhn) Groves and Skolko) was first defined in Puerto Rico [18] and later reported in some other parts of the world, e.g., Mauritius [19]. In the following 14 years, A. dauci has been reported in many other countries including India [20,21], the United States [22], Algeria [23], and recently in Brazil [24]. Coriander plants and seeds have recently been found to be infected with A. dauci [7,25].…”
Section: Introductionmentioning
confidence: 99%